Development of Critical Thinking Skills Instruments on News Text Material - Hasibuan, Ahmad Yamin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Critical thinking skills is one of the skills that are needed in studying the text news. Considering the amount of news that appears every day in various media such as television, internet, and mass media others with various themes ranging from events that occur in society up to the information global challenges of various parts of the world. The goal of this research is to create accurate and valid news text instruments. Research and Development (RD) using the 4D model is the methodology employed in this study. Define, Design, Develop, and Disseminate are some of the stages. The study's findings show that the news text instrument produced is practical to use. Because it is greater than 0.325 and the reliability is greater than 0.6, the empirical validation results indicate that there are 15 valid claims.